Gastroparesis in a young diabetic patient - Kovačič, Primož (Radiology and oncology (Ljubljana), 2002)
Background. Gastroparesis is defined as a delay in emptying of contents from the stomach and occurs in a variety of conditions, e.g. after vagotomy or in systemic diseases such as diabetes mellitus, scleroderma and amyloidosis. The purpose of this paper is to present the radiologic examination, a simple, reliable and noninvasive method as an alternative to other methods for the assessment of gastric emptying. Case report. A twenty-one years old female wasadmitted because of suspected autonomic neuropathy. She had insulin dependent diabetes mellitus type 1 for the last ten years. At the time of admission she was complaining of nausea, vomiting weakness and occasional dizziness. A barium study of oesophagus and stomach was performed: oesophagus was dilated and aperistaltic, remnants of food were seen in aperistaltic stomach but no obstruction, causing delayed emptying, was found. Conclusions. Scintigraphy is at the present the standard technique for the assessment of gastric emptying. Ultrasonography, magnetic resonance imaging; electrogastrography, gastroduodenal manometry and emptying of radiopaque pellets are also used for the evaluation of gastric motility in cases of delayed gastric emptying. The role of barium studies remains to be established.
Keywords: Adult; Barij; Barium; Complications; Contrast media; Diabetes mellitus; diagnostika; Gastroparesis; Gastropareza; Kontrastna sredstva; Odrasli; Radiography; Sladkorna bolezen; želodec